2019
DOI: 10.6004/jnccn.2018.7266
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of the 21-Gene Assay Among Women With Node-Positive, Hormone Receptor−Positive Breast Cancer

Abstract: Background: This study assessed uptake of the Oncotype DX 21-gene assay over time and characterized which sociodemographic and clinical factors are associated with test uptake among women with lymph node−positive (LN+), hormone receptor−positive, HER2-negative breast cancer. Methods: Invasive breast cancer cases diagnosed in 2010 through 2013 were included from a SEER database linked to 21-gene assay results performed at Genomic Health’s Clinical Laboratory. Factors associated with 21-gene assay uptake were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Our data is consistent with previous studies [25][26][27][28][29] demonstrating decreased use of ODX RS with increasing age. Similar to previous reports 30 , we found that median ODX RS was similar across age and nodal status.…”
Section: Discussionsupporting
confidence: 93%
“…Our data is consistent with previous studies [25][26][27][28][29] demonstrating decreased use of ODX RS with increasing age. Similar to previous reports 30 , we found that median ODX RS was similar across age and nodal status.…”
Section: Discussionsupporting
confidence: 93%
“…There were 34.8%, 20.6%, and 12.7% of patients with one-, two-, and three-LN metastases who had 21-gene testing, respectively. Similar results were found from the study by Roberts et al., which included 30,410 patients with N+ BC, and the receipt of 21-gene testing was low in patients with high-risk factors ( 29 ). Our findings, along with the above study, showed that clinicians may choose not to perform 21-gene testing in more advanced patients with historical indications for chemotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…In this light, it is highly relevant to underline that GEPs are not accessible (i.e. $4.000 per 21-GS, $3.900 per 70-GS) nor applicable for every IBC patient [35][36][37][38][39][40][41][42]. For example, probably only up to half of the eligible women in the US receive GEP-testing [40,41].…”
Section: Discussionmentioning
confidence: 99%